2006
DOI: 10.1016/j.ejcts.2006.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic skeletonization on internal thoracic and gastroepiploic arteries for coronary artery bypass grafting

Abstract: Ultrasonic complete skeletonization with the harmonic scalpel may retain smooth muscle function of skeletonized grafts, whereas endothelial function of ultrasonic skeletonized grafts may be significantly compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This result was to be expected as previous studies showing that the vasodilator action of atrial natriuretic peptide is endothelium-independent and associated with increased cellular levels of cGMP as a result of activation of a particulate rather than a soluble guanylate cyclase in smooth muscle cells [13,14]. Endothelium-independent action of carperitide is advantageous in operation theaters as the endothelium of bypass grafts are easily and frequently injured during harvest and anastomoses in coronary artery bypass surgery [15].…”
Section: Commentsupporting
confidence: 77%
“…This result was to be expected as previous studies showing that the vasodilator action of atrial natriuretic peptide is endothelium-independent and associated with increased cellular levels of cGMP as a result of activation of a particulate rather than a soluble guanylate cyclase in smooth muscle cells [13,14]. Endothelium-independent action of carperitide is advantageous in operation theaters as the endothelium of bypass grafts are easily and frequently injured during harvest and anastomoses in coronary artery bypass surgery [15].…”
Section: Commentsupporting
confidence: 77%
“…Although this study has not been included in our data synthesis, as it contains no clinical data, we felt it contained some important results. They provide the first evidence that ultrasonic skeletonization is probably more traumatic to endothelial function than a conventional harvesting technique [40], and concluded that those who perform skeletonization should only employ vasodilators whose mode of action is not reliant on intact endothelial function to improve graft patency in the early post operative period.…”
Section: Resultsmentioning
confidence: 99%
“…In the cardiac surgery field, it is currently used for radial, thoracic, and gastroepiploic artery harvesting, pericardial resections, and tissue dissection during redo cases. [2][3][4] In other surgical specialties its applications are widely diverse, from division of splenic vessels, to thoracic duct division, thoracoscopic sympathectomies, lung resections, hepatectomies, pancreatic resections, partial and total nephrectomies, varicocelectomies, and hysterectomies, among many others. It has been proved to be a safe tool in terms of hemostasis, even when used to divide large systemic arteries, such as the splenic artery, or the feeding arteries of pulmonary sequestrations.…”
Section: Discussionmentioning
confidence: 99%